Peran Bank Wakaf Mikro Syariah Di Pesantren Mawaridussalam Dalam Pemberdayaan Ekonomi Masyarakat - Isnaini Harahap; M Mailin; Salisa Amini (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2019)
Poverty is no longer a new thing and has always been a complex problem for Indonesian people. Besides poverty there is also an economic inequality that usually occurs in rural areas. The community actually needs economic affairs as a solution to say the economy. Pesantren is an institution that educates not only the students but also the surrounding community. The presence of pesantren in the middle of the community, especially rural in addition to giving influences in the religious surroundings, also began to revive its economy. Limited business capital is sometimes a matter of people who want to start business. The government also started to look at the Pesantren for the program to empower the economy of people who have the majority of rural poor to be established by the Bank. The government aims to establish the Bank Wakaf Micro Sharia in Pesantren so that the pesantren has a role to the community so that it has strong attachment as well as a container empowering its community economy. But all is not that easy, there is still a challenge when the empowerment process will or is being executed. For that need to be careful with the aim to know the role of Pesantren Mawaridussalam through the business unit of the Bank WAKAF Micro Sharia towards community empowerment, to know the challenge of pesantren Mawaridussalam in community empowerment through The business unit micro Sharia Bank. The research methods used are observation, interviews, with a qualitative descriptive approach. The results of the study showed that pesantren through Bank Wakaf Micro Sharia has a role in empowering the community by providing business capital loans, escape from the trap of moneylenders and the flower or RIBA system and to add the religious sciences already Clearly give people welfare.